The Limit to Politics of Ethnicity? Migration and Upland Transformation in Central Sulawesi - Abdulkadir Sunito, Melani; Adiwibowo, Soeryo; Soetarto, Endriatmo; A.Kinseng, Rilus; Foley, Sean (Sodality: Jurnal Sosiologi Pedesaan, 2017)
ABSTRACTAlthough in early 2000s ethnic politics was used to gain access to land inside the National Park, thus transformed land use in an upland village in Central Sulawesi, a decade later it losts its role as the main driver to further expansion of agriculture-land. Using political ecology approach, this paper discusses territorialization through politics of ethnicity and ethnicity/identity as mechanism to access. The findings indicated that ethnic politics are enabled, and constrained, by certain conditions within the community as well as from external situation. In the latter trajectory of upland transformation, politics of ethnicity are constrained by an alteration of ethnic groupings as new migrants came to the village community, a ‘leveling-off playing field’ in land access and high-external input agriculture commodities, as well as a change in forest-policy.Keywords: ethnic politics, migration, upland transformationABSTRAKMeski pada permulaan tahun 2000an politik etnisitas digunakan untuk memperoleh akses atas tanah hutan di dalam Taman Nasional, lantas merubah penggunaan lahan pada suatu desa dataran tinggi di Sulawesi Tengah, satu dekade setelahnya politik etnisitas tak lagi berperan dalam ekspansi lanjutan tanah pertanian itu. Menggunakan pendekatan ekologi politik, tulisan ini membahas teritorialisasi melalui politik etnisitas dan penggunaan kuasa etnisitas/identitas sebagai mekanisme untuk mengakses. Temuan penelitian menunjukkan bahwa politik etnisitas dimungkinkan, ataupun dibatasi, oleh kondisi-kondisi di dalam komunitas maupun situasi eksternal. Pada trajectory transformasi desa yang belakangan, politik etnisitas dibatasi oleh perubahan pengelompokan etnis akibat migrasi baru pada komunitas desa yang kian beragam etnis, suatu leveling-off playing field dalam akses atas tanah dan budidaya komoditas pertanian tinggi-input yang mengarah pada pemerataan kesempatan ekonomi dan pendapatan, serta perubahan dalam kebijakan kehutanan.Kata kunci: politik etnisitas, migrasi, transformasi dataran tinggi pedalaman